Group singing and its effect on cortisol, alpha amylase, oxytocin, and pain threshold in patients with Parkinson's disease - Mallik, Adiel; Raessi, Tara; Good, Arla; Pachete, Alex; Russo, Frank A. (Frontiers in Neuroscience, 2025)
BackgroundParkinson's disease (PD) is a neurodegenerative disorder that causes motor deficits, including rigidity and tremors. Pain is also a common problem for people with PD that may arise from their dopamine deficit. Some patients with PD experience temporary relief from pain through group singing, which has also been shown to mitigate vocal challenges related to PD. However, no work has been conducted to elucidate the neurochemical mechanisms of action on the pain threshold. Here, we examined whether the effects of group singing on cortisol, alpha amylase, and oxytocin levels are associated with changes in pain thresholds in patients with PD.MethodsParticipants with PD (n = 14) participated in a 12-week singing program involving weekly 45-min group singing sessions in the early afternoon. Data collection, involving saliva samples and pain thresholds, was performed pre- and post-session in the 2nd (Session 1), 7th (Session 2), and 12th (Session 3) weeks of the program. Saliva samples were collected before and after each session by using the passive drool method. The pain threshold was assessed before and after each session by applying pressure to the finger using a dolorimeter. Saliva samples were used to assess salivary cortisol (sCORT), alpha amylase (sAA), and oxytocin (sOXT). Pain threshold, sCORT, sAA, and sOXT change scores were calculated for each session by subtracting the pre-session value from the post-session value.ResultsThree mixed linear model analyses were performed to assess whether sCORT, sAA, and sOXT were associated with increased pain threshold. We found that group singing led to a significant reduction in sCORT and sAA. We also found that reductions in sCORT were significantly related to an increase in the pain threshold (p < 0.05). However, we did not observe any relationship between pain threshold increases and sAA or between pain threshold and sOXT.ConclusionGroup singing significantly increases the pain threshold in patients with PD, and this increase may be mediated through a reduction in cortisol levels.